Pendampingan Penggunaan Aplikasi AI Sebagai Upaya Peningkatan Inovasi Dalam Pengajaran Guru Di Sekolah - Hasnani; Widya Wulandari; Sitti Hajrah; Maria Enjelina Debibilian; Waode Amaliah (ABDI SAMULANG: Jurnal Pengabdian Kepada Masyarakat, 2024)
The need for innovation in learning in schools is increasingly urgent with the development of information and communication technology. In an effort to improve the quality of learning, approaches based on artificial intelligence (AI) have become a highlight in modern education. This Community Service aims to provide assistance in using AI applications as an effort to increase innovation in teacher teaching in schools. This assistance includes training in using AI applications, integrating technology into the learning process, and creating content that meets curriculum needs. With the help of this mentoring, educators can harness the potential of AI to increase learning effectiveness and provide more engaging and relevant learning experiences for students. The results of this Community Service activity show that the partners (teachers) are very satisfied with the training provided. This is also supported by very effective interactions during activities. Mentoring is expected to make a positive contribution to improving the quality of education at the Education Unit level, especially for teachers at Pannara State Elementary School, Makassar City, South Sulawesi.